An enzymatic method for harvesting functional melanosomes after keratin extraction – maximizing resource recovery from human hair - Zhang, Nan (2021)
Hair contains about 80% keratins and 1–3% melanin packaged in melanosomes. Both of these are high-value and functional raw materials that have potential applications in wide-ranging fields. While keratin extraction has been widely refined, efficient methods of melanosome extraction are limited. The extraction of melanosomes requires complete removal of keratin, thus combining keratin extraction and melanosome isolation is logical. Herein, a successive process to harvest melanosomes after keratin extraction from human hair waste was developed. The yield of melanosomes was about 1.3% of the total hair mass. The structure of harvested melanosomes is well preserved based on surface morphology and interior ultrastructural observations using electron microscopy. The chemical structure, ultraviolet (UV)-filtering ability, and thermal stability of the melanosomes are examined to demonstrate preservation of native functions. Our strategy of combining melanosome isolation with keratin extraction is shown to be effective and significantly improves the total resource recovery efficiency from human hair waste.